2020
DOI: 10.17977/jptpp.v5i9.14038
|View full text |Cite
|
Sign up to set email alerts
|

Teacher’s Perception toward the Use of English for Communication Science Book

Abstract: <table width="645" border="1" cellspacing="0" cellpadding="0" align="left"><tbody><tr><td valign="top" width="439"><p><strong>Abstract: </strong>This study aimed at investigating the teachers’ perception toward the use of English for Communication Science book and how it facilitates the teaching learning process. Descriptive qualitative research was applied in this study. According to the data obtained from questionnaire and interview, the textbook has fulfilled severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…To be able to address the research problem of this study, it is very important to identify the teacher's perception toward the textbook they teach and their experience in that area. According to numerous studies on the textbooks, their role in language teaching and the teacher's viewpoint in the process [9]. The findings of several previous studies showed that the textbook used in the classroom is considered suitable to the students' need, teachers' need, syllabus and examination.…”
Section: Teacher's Role In Evaluating the Textbookmentioning
confidence: 99%
See 1 more Smart Citation
“…To be able to address the research problem of this study, it is very important to identify the teacher's perception toward the textbook they teach and their experience in that area. According to numerous studies on the textbooks, their role in language teaching and the teacher's viewpoint in the process [9]. The findings of several previous studies showed that the textbook used in the classroom is considered suitable to the students' need, teachers' need, syllabus and examination.…”
Section: Teacher's Role In Evaluating the Textbookmentioning
confidence: 99%
“…Additionally, the importance of language textbooks in the development of target language pragmatic knowledge is also significant. However, the previous analyses of language textbooks have pointed out that many textbooks tend to offer classroom learners little opportunity for learning L2 pragmatics [6][7][8][9][10][11][12]. The mentioned studies clarify that language textbooks presents speech acts unfairly.…”
Section: Introductionmentioning
confidence: 98%